Thyroid Cytology: The Japanese System and Experience at Yamashita Thyroid Hospital - Shinya Satoh; Hiroyuki Yamashita; Kennichi Kakudo (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
In Japan, fine-needle aspiration (FNA) cytology is the most important diagnostic modality for triaging patients with thyroid nodules. A clinician (endocrinologist, endocrine surgeon, or head and neck surgeon) generally performs FNA cytology at the outpatient clinic, and ultrasound (US)-guided FNA is widespread because US is extremely common and most clinicians are familiar with it. Although almost all FNA thyroid samples are examined by certified cytopathologists and pathologists, some clinicians assess cytological specimens themselves. In Japan, there are two clinical guidelines regarding the management of thyroid nodules. One is the General Rules for the Description of Thyroid Cancer (GRDTC) published by the Japanese Society of Thyroid Surgery (JSTS) in 2005, and the other is the national reporting system for thyroid FNA cytology published by the Japan Thyroid Association in 2013 (Japanese system). Although the Bethesda System for Reporting Thyroid Cytopathology (Bethesda system) is rarely used in Japan, both the GRDTC and Japanese system tried to incorporate the Bethesda system so that the cytological diagnoses would be compatible with each other. The essential point of the Japanese system is stratification of follicular neoplasm (FN) into three subgroups based on cytological features in order to reduce unnecessary diagnostic thyroidectomy, and this system has been successful in stratifying the risk of malignancy in FN patients at several high-volume thyroid surgery centers. In Japan, the measurement of thyroglobulin and/or calcitonin in FNA needle washings is often used as an adjunct for diagnosis of possible cervical lymph node metastasis when FNA cytology is performed.